1838 Ark. Rev. Stat. 587 - (:unkn) unknown (My University, 1838)
§ 18: Provided that every gun, rifle, weapon of any kind, ammunition found in the possession of any "free negro or mulatto" not having a license may be seized and violators fined not exceeding twenty dollars.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES